JOMH 2021
DOI: 10.31083/jomh.2021.073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of six weeks of stable versus unstable multi-dimensional surfaces balance training on passing skills and balance performance in young male basketball players

Abstract: Background and objective: Adolescence is a period when balance and coordination decrease as a result of rapid musculoskeletal growth. These changes may affect various sports-specific skills, including balance. This study aimed to examine the changes in balance performance and basketball passing speed in male youth basketball players following six weeks of balance training performed on unstable versus stable surfaces. Methods: Twenty-five male basketball players, mean age 15.53 ± 0.57 years, participated in bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Another study on visualisation training discovered an average improvement of 33% in the free throw ability of basketball extracurricular students (Profaviola et al, 2019). In contrast to stable surfaces, doing balance exercises on unstable surfaces resulted in higher passing accuracy and balance performance improvement, according to a third study on balance training (Fisek & Agopyan, 2021). According to this research, basketball players' technical skills essential for individual player development and team success can be efficiently improved through focused training programmes.…”
Section: Resultsmentioning
confidence: 69%
“…Another study on visualisation training discovered an average improvement of 33% in the free throw ability of basketball extracurricular students (Profaviola et al, 2019). In contrast to stable surfaces, doing balance exercises on unstable surfaces resulted in higher passing accuracy and balance performance improvement, according to a third study on balance training (Fisek & Agopyan, 2021). According to this research, basketball players' technical skills essential for individual player development and team success can be efficiently improved through focused training programmes.…”
Section: Resultsmentioning
confidence: 69%
“…In this sense, the unstable surface could entail excessive postural sway fluctuations for the participants of our study ( Davids et al, 2004 ), which resulted in higher levels of stress on the system ( Moreno & Ordoño, 2015 ). Conversely, previous studies that have reported benefits from the use of unstable surfaces were conducted with young or inexperienced athletes ( Aydin & Revans, 2019 ; Fisek & Agopyan, 2021 ; Zacharakis et al, 2020 ), except for Caballero, Luis & Sabido ’s study ( 2012 ). Furthermore, studies conducted with experienced athletes have not found additional improvements caused by training on unstable surfaces ( Alicia Nian, 2017 ; Sillero et al, 2022 ), except for Hung et al ’s study ( 2021 ), which did not perform a group comparison.…”
Section: Discussionmentioning
confidence: 92%
“…Based on this rationale, increasing motor variability during practice through the manipulation of the support base could enable highly functional behavior, revealing useful sources of information to regulate the movement ( Davids et al, 2004 ). However, as far as the authors know, little empirical evidence supports the usefulness of inducing motor fluctuations through unstable surface to promote faster learning in throwing ( Fisek & Agopyan, 2021 ; Zacharakis et al, 2020 ) or related tasks as shooting ( Aydin & Revans, 2019 ; Hung et al, 2021 ), while other works do not find any additional benefits ( Alicia Nian, 2017 ; Caballero, Luis & Sabido, 2012 ; Sillero et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Being able to move swiftly and change directions helps in avoiding defenders and creating passing lanes ( Spiteri et al, 2015 ). Balance is essential when making passes while in motion or after a quick COD ( Nikolaos et al, 2012 ; Fisek and Agopyan, 2021 ). Basketball dribbling skills are not only related to ball control, vision, and court awareness but also depend on various physical fitness factors such as hand speed, coordination, changes in pace and speed, and directional control ( Ferioli et al, 2020 ; Vencúrik et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%